Indonesia : 2020 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Indonesia. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2021)
Indonesia has responded with a bold and comprehensive policy package to cushion the impact of the COVID-19 pandemic. The economy rebounded in the third quarter of 2020, and the economic recovery is projected to strengthen in 2021 and 2022. Strong policy support and an improving global economy will be the main drivers initially, and greater mobility and confidence will follow with the planned vaccination program in 2021. The uncertainty surrounding the growth outlook is larger than usual. Early completion of a widespread vaccination program is an upside risk, while a protracted pandemic remains a downside risk. The macro-financial fallout of the pandemic and economic downturn could be larger than expected, and credit conditions could be slow to improve. Ongoing reforms aimed at promoting investment are expected to help mitigate the scarring effects from the pandemic and put the economy on a sustained growth path that builds on Indonesia's favorable demographics.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet